Swedish Tax Rates, Labor Supply, and Tax Revenues - Stuart, Charles E. (Journal of Political Economy, 1981)
Effective marginal tax rates on labor income for the "representative" Swede have increased from roughly 50 percent in 1959 to 80 percent today. The effects of this increase in the level of taxation are examined using a two-sector model parameterized to correspond to the Swedish economy. The model contains a single household which allocates labor to either taxed (essentially market) or untaxed (largely household) uses. The estimated long-run effects are sufficient to explain up to 75 percent of the recent decline in the measured growth rate of the Swedish GNP. Calculations of total tax revenues are also derived from the model. These peak when the tax rate is approximately 70 percent, indicating that Sweden is presently on the downward-sloping portion of its "Laffer Curve."